El Positivismo y el Materialismo Dialéctico: vínculos, tensiones y puntos de discusión. Hacia un principio de análisis a partir de la polémica de Voloshinov (1929) con el ‘objetivismo abstracto’ en Lingüística - Condito, Vanesa (2014)
The paper aims to critically review the arguments proposed by V. Voloshinov in the The Marxism and the philosophy of the language (1929) in relation to the approach he called 'abstract objectivism', which its central exponent in the Course of General Linguistics is F. de Saussure (1916). Specially, we will examine how the Voloshinov’s text entails certain epistemological assumptions of dialectical materialism and how it is precisely from there that argument criticism Saussurean linguistics, read from a rationalism positivism dominated by imprinting his circumstances